KAMUBISAKUL application to Facilitate students with hearing impairments to follow the lecture process - Utomo Utomo; Dewi Ratih Rapisa; Eviani Damastuti; Hayatun Thaibah (Journal of ICSAR, 2021)
There are 20 students with special needs at Lambung Mangkurat University, 9 of which are students with hearing impairments. The obstacles experienced by students with hearing impairments during the lecture process are mainly communication problems, especially receptive language (the ability to understand the interlocutor). Not all lecturers understand the needs and characteristics of students with hearing impairments and sign language skills. However, students with special needs are required to follow and succeed in meeting the learning targets set by the lecturer. Therefore we need assistive technology (assistive) that can help students with special needs. In this case, students with hearing impairments make it easier for them to learn and achieve the expected targets. This research aims to develop assistive technology for students with hearing impairments to attend the lecture process. This study used a descriptive method with a qualitative approach, and the type of research used in this study was the Research and Development (RnD) type. This study selected research subjects using the purposive sampling technique to select nine students with hearing impairments at Lambung Mangkurat University. The stages in this research begin with: (1) Literature Study; (2) Needs Analysis; (3) Assessment; (4) FGD or Application Design; (5) Making the KAMUBISAKUL Application; (6) Trial of KAMUBISAKUL Application; (7) Dissemination of the KAMUBISAKULl Application; and (8) Evaluation. Assistive technology development carried out by the research team resulted in an application called KAMUBISAKUL. Based on research, this application is helpful for students with hearing impairments in interpreting essential terms used in lectures. These terms relate to information about the course enrollment flow, UKT (Tuition Fee) payment, lectures, names of college’s rooms. This application is helpful for students with hearing impairments in interpreting essential terms used in lectures. These terms relate to information about the course enrollment flow, UKT payment, lectures, names of rooms in lectures. This application is helpful for students with hearing impairments in interpreting essential terms used in lectures. These terms relate to information about the course enrollment flow, UKT payment, lectures, names of rooms in lecturers.